(untitled) (Indian Journal of Psychology & Education, 2020)
The current study aimed to investigate whether Sultan Qaboos University (SQU) students’ college experiences impact the adaptation of academic identities. It is assumed that Sultan Qaboos University academic system is different from high-school academic system. The differences are observed in terms of the curriculum structure, grading system, teaching style, and culture orientation. A sample of 2468 students completed self-report measures. These were self-efficacy and academic identity measure. Descriptive research design was used. The analysis supports the assumption that academic identity status is shaped through college experiences. Interestingly, the academic identity status does account for variance in the students’ GPA. The results revealed that identity foreclosure is gradually less adopted as students move on toward their degree completion. The interaction analysis revealed that the main effect of GPA on achievement identity was qualified by study year. Sultan Qaboos University students gain more confidence as they move toward degree completion. More research is needed in regard to students failing in identity restructuring, as well as strategies deployment.